Clinical Findings of Anterior Segment Spectral Domain Optical Coherence Tomography Images in Cytomegalovirus Corneal Endotheliitis. Issue 4 (April 2017) - Kobayashi, Reiko; Hashida, Noriyasu; Soma, Takeshi; Koh, Shizuka; Miki, Atsuya; Usui, Shinichi; Maeda, Naoyuki; Nishida, Kohji
Abstract : Purpose: To evaluate the morphological characteristics of posterior corneal regions including keratic precipitates in eyes with cytomegalovirus (CMV) corneal endotheliitis using anterior segment spectral domain optical coherence tomography (SD-OCT). Methods: Thirteen eyes of 13 patients with polymerase chain reaction–proven CMV corneal endotheliitis were included in this study. Slit-lamp images and anterior segment SD-OCT images of the posterior cornea were obtained to analyze the clinical characteristics of corneal structures and keratic precipitates. Morphological changes in the posterior cornea throughout the course of an antiviral treatment were also investigated. Results: Anterior SD-OCT images showed protruding structures at the posterior cornea. These protruding structures exhibited dendritic, dome-shaped, quadrangular, or saw-tooth appearance, and reflectivity of these structures was high. Reflectivity of posterior corneal images including the endothelium and deep stromal corneal regions were also high (76.9%). Because corneal inflammation and corneal edema improved, the protruding structures and high-intensity regions of posterior corneal images were resolved after a course of antiviral treatment. Conclusions: The anterior segment SD-OCT examination represents a useful noninvasive alternative to diagnose and monitor CMV corneal endotheliitis.